Implementation of Peer Counselors in Strengthening Mental Health at PIK-R Sei Nagalawan Village - Nur Ainun Damanik; Sri Ngayoumi Yudha Wastuti (Universitas Muhammadiyah Enrekang, 2024)
Adolescent mental health is a major concern in an effort to improve the welfare of the younger generation. Through the PIK-R program established by BKKBN, adolescents gain knowledge and life skills in order to live a healthy and prosperous life. This study aims to implement peer counselors as a strategy to strengthen adolescent mental health in PIK-R Sei Nagalawan Village. The research method used is qualitative descriptive with case study techniques. Research data were obtained through interviews, observation and documentation. The results showed that the implementation of peer counselors in PIK-R Sei Nagalawan Village had a positive impact on improving adolescent mental health in Sei Nagalawan Village. Where Nagalawan village teenagers already have good skills in solving problems, support each other in their groups, are more confident in expressing their ideas, are able to discuss and accept other people's opinions, and there is an improvement in their life skills. Thus, peer counselor services are an effective step in strengthening adolescent mental health, and improving the overall well-being of the younger generation.